INTERNALISASI NILAI PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL DI SMA NEGERI 8 MALANG (VICRATINA, 2021)
Internalization of the value of multicultultural-based Islamic religious education is one of the models of islamic religious education learning that relates the existence of cultural diversity as the reality of life given by God to man. This understanding aims to produce learners to be tolerant, look after each other and respect each other above all differences. This study aims to illustrate how learning strategies, internalize the value of multicultural-based Islamic religious education and identify how hasi internalize the value of multicultural-based Islamic religious education at SMA Negeri 8 Malang. This research uses qualitative methods with a case study approach. Data collection is conducted by observation, interview and documentation. Based on the results of the study, internalize the value of multicultural-based Islamic religious education at SMA Negeri 8 Malang through learning in the classroom, namely; teachers are universal and do not discriminate against students, teachers give all students the opportunity to get their religious lessons. While outside the classroom is through extracurricular activities and social activities. The result of the ineternization is the creation of a comfortable and conducive learning atmosphere, avoiding conflicts between students and teachers, the realization of harmony and harmony in differences, the realization of a culture of tolerance and mutual cooperation.